Answer:
-6x + 17
Step-by-step explanation:
-(6x - 17)
= -6x + 17
=》Negative × negative = positive
=》 Positive × negative = negative
Hope it helps ⚜
(2(8)-12)+(12(8)(2)-10)
(16-12)+(132-10)
4+122=126
THE ANSWER WOULD BE 126 :D
Answer:
f ( x ) = ( x - 5 ) ² - 20
Step-by-step explanation:
1- Add the same value to both sides
f ( x ) = x ² - 10x + 5
2- Add 25 to the expression
f ( x ) + ? = x ² - 10x + ? + 5
3- Add 25 to the left-hand side
f ( x ) + ? = x ² - 10x + 25 + 5
4- Factor the expression
f ( x ) + 25 = x ² - 10x + 25 + 5
5- Move the constant to the right
f ( x ) + 25 = ( x - 5 ) ² + 5
6- Calculate
f ( x ) = ( x - 5) ² + 5 - 25
It will help me a lot if you count me as brainlist anyways good luck!
<span>Line LM= x+5 and is proportional to line QR which equals 30. Line LN= 50 and is proportional to line QS which equals 75.
</span>The answer is 11.3
Use the property of distribution:
a(b+c) = ab + ac
4(4a+5) = 4(4a) + 4(5)
4(4a+5) = 16a + 20
Hope that helps :)